Acute Intermittent Porphyria – A Rare Case with Neurovisceral Symptoms (Journal of Armed Forces Medical College, Bangladesh, 2022)
Acute intermittent porphyria (AIP) is an autosomal dominant disorder resulting from partial deficiency of the porphobilinogen deaminase affecting the production of heme. It produces acute neurovisceral symptoms. The diagnosis of AIP is difficult. Symptoms are often nonspecific.As the penetrance is low in AIP, positive family history of disease may be absent. So high index of suspicion is required to diagnose AIP. Combination of neurologic and visceral symptoms gives clue to the diagnosis. In December 2018, we have diagnosed a case of Acute intermittent porphyria who presented with acute abdomen, hypertension, tachycardia and convulsion. His urine colour turned to purple red on exposure to sunlight. He had hyponatremia. MRI of brain revealed features of Posterior Reversible Encephalopathy Syndrome (PRES) and EEG was suggestive of focalseizure. Urine porphoblinigen was positive. He was treated with IV glucose, DNS, high carbohydrate diet, newer antiepileptic drug, opioid analgesic, antihypertensive medication and other supportive and symptomatic measures. Ultimately his condition improved gradually and discharged with advice to continue medicine and periodic follow up.JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 94-96